2018
DOI: 10.1002/jlb.3mr0118-034r
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-γ in innate and adaptive lung immunity

Abstract: The transcription factor PPAR-γ (peroxisome proliferator-activated receptor-γ) is a key regulator of lung immunity exhibiting multiple cell type specific roles in controlling development and function of the lung immune system. It is strictly required for the generation of alveolar macrophages by controlling differentiation of fetal lung monocyte precursors. Furthermore, it plays an important role in lung allergic inflammation by licensing lung dendritic cell t helper 2 (Th2) priming capacity as well as acting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 46 publications
(93 reference statements)
0
21
0
2
Order By: Relevance
“…1), the transcription factor peroxisome proliferator-activated receptor-γ (PPARγ) is being increasingly recognized as a modulator of lipid metabolism linked to inflammation and immunity, particularly in tissueresident macrophages. Early evidence indicated that PPARs inhibit proinflammatory responses in macrophages 120 , but the role of PPARγ seems to be much more nuanced and is influenced by the target macrophage lineage 121 . PPARγ is required for tissue macrophagemediated clearance of S. aureus skin infections and for control of Pseudomonas aeruginosa in the lung 122 , and it is implicated in both the control and progression of M. tuberculosis infection, dependent on the model [123][124][125][126] .…”
Section: Macrophage Ontogeny and Metabolismmentioning
confidence: 99%
“…1), the transcription factor peroxisome proliferator-activated receptor-γ (PPARγ) is being increasingly recognized as a modulator of lipid metabolism linked to inflammation and immunity, particularly in tissueresident macrophages. Early evidence indicated that PPARs inhibit proinflammatory responses in macrophages 120 , but the role of PPARγ seems to be much more nuanced and is influenced by the target macrophage lineage 121 . PPARγ is required for tissue macrophagemediated clearance of S. aureus skin infections and for control of Pseudomonas aeruginosa in the lung 122 , and it is implicated in both the control and progression of M. tuberculosis infection, dependent on the model [123][124][125][126] .…”
Section: Macrophage Ontogeny and Metabolismmentioning
confidence: 99%
“…PPARγ can stimulate the differentiation of pre‐adipocytes into mature adipocytes and is closely related to adipogenesis in mature adipocytes . The beneficial role of PPARγ in regulation immunity was summarized by Samuel Philip Nobs, Chung, Abdelrahman, Giaginis and Staels . PPARγ inhibits pro‐inflammatory responses by macrophages, DCs, and T cells.…”
Section: Function and Cellular Roles Of Pparγmentioning
confidence: 99%
“…PPARγ promotes lipogenesis during anabolism by acting on the adipose tissue. Besides, this receptor is a participant in inflammatory reactions [4] and a regulator of the immune system in the lungs [10,40]. The binding of specific ligands to PPARγ regulates the transcription of target genes and inhibits the activation of immune cells and the expression of inflammatory factors [8].…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%